1995
DOI: 10.1021/bi00046a037
|View full text |Cite
|
Sign up to set email alerts
|

Self-Association of the Molecular Chaperone HSC70

Abstract: The self-association properties of the molecular chaperone HSC70 have been analyzed by a wide range of biochemical and biophysical techniques. Nondenaturing gel electrophoresis and cross-linking studies show the presence of multiple species going from monomer to at least trimer. Size-exclusion chromatography gives two overlapping peaks, a major one corresponding to species having the molecular mass of monomer (70 kDa) and a minor broad one corresponding to species with a molecular mass range of 150-300 kDa. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 40 publications
8
56
0
Order By: Relevance
“…The sedimentation coefficient measured for ␣-Syn (1 S) is compatible with the molecular mass of a natively unfolded 14-kDa polypeptide. The species we observe for Hsc70 have been previously described and correspond to monomeric, dimeric, and oligomeric Hsc70 (31). Determination of sedimentation coefficients gives valuable information on the hydrodynamic shape of protein complexes and conformational changes within these complexes.…”
Section: Volume 286 • Number 40 • October 7 2011mentioning
confidence: 54%
“…The sedimentation coefficient measured for ␣-Syn (1 S) is compatible with the molecular mass of a natively unfolded 14-kDa polypeptide. The species we observe for Hsc70 have been previously described and correspond to monomeric, dimeric, and oligomeric Hsc70 (31). Determination of sedimentation coefficients gives valuable information on the hydrodynamic shape of protein complexes and conformational changes within these complexes.…”
Section: Volume 286 • Number 40 • October 7 2011mentioning
confidence: 54%
“…Initially, we found that Hsp90 was predominantly dimeric and FKBP52 monomeric, both were anticipated. Recently there has been some controversy over the oligomeric state of Hop reported as dimeric (6,20,34) or monomeric (22,35) and Hsp70 can form high oligomeric species under some conditions (36). We have shown that under the conditions used here both proteins are monomeric.…”
Section: Discussionmentioning
confidence: 65%
“…Protein Expression and Purification-Recombinant HSC70 was expressed and purified as described previously (30,34). The recombinant NH 2 -terminal domain of HSC70 was expressed and purified as described for HSC70 except that the first ion exchange chromatographic step was replaced by a 60% ammonium sulfate precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation, the ammonium sulfate concentration of the supernatant was adjusted to 80%, and the sample was submitted to centrifugation. The resulting pellet was resuspended in 20 mM Tris-HCl, pH 7.5, 20 mM KCl, 1 mM ␤-mercaptoethanol, and 3 mM MgCl 2 , dialyzed in the same buffer, and applied onto an ATP-agarose affinity column as described previously (30,34).…”
Section: Methodsmentioning
confidence: 99%